18. THE EFFECTIVENESS OF DEXAMETHASONE AND ONDANSETRON IN PREVENTION OF POSTOPERATIVE NAUSEA AND VOMITING IN PATIENT UNDERGOING LAPAROSCOPIC CHOLESCYSTECTOMY AT GENERAL HOSPITAL OF CENTRAL HIGHLANDS (Vietnam Journal of Community Medicine, 2024)
Background: Endoscopic cholecystectomy is a routine surgical treatment of gallbladder stones. Endoscopy is less invasive than open surgery, but the incidence of postoperative nausea and vomiting is higher than open surgery, about 40-70%. The prophylactic efficacy of Ondansetron for postoperative nausea and vomiting has been demonstrated through numerous studies. Dexamethasone is an easy-to-find and cheap drug, but has not been widely used in the prevention of nausea and vomiting after surgery.Research objects and methods: Randomized clinical intervention study with control group, single blind. Comparison of nausea - vomiting prophylaxis efficacy of Dexamethasone and Ondansetron in the first 24 hours after laparoscopic cholecystectomy in 208 patients. Group D (Dexamethasone) 105 patients received 4 mg of Dexamethasone intravenously upon induction, Group O (Ondansetron) 103 patients received 8 mg of Ondansetron intravenously upon induction. All patients received postoperative care and treatment according to the same protocol. Patients were assessed for postoperative nausea - vomiting during the first vomiting period. Monitor for vomit prevention medicine side effects such as headache, dizziness...Results: Nausea - vomiting prophylaxis effect of Dexamethasone and Ondansetron in the first 24 hours after laparoscopic cholecystectomy, postoperative nausea-vomiting rates of patients undergoing laparoscopic cholecystectomy with one or more risk factors according to Apfel, in the group prophylactic with Dexamethasone 4 mg, 16.5% compared to the group prophylactic with Ondansetron 8 mg, 20%, were similar.Conclusions: The nausea - emesis prevention effect of Dexamethasone 4 mg and Ondansetron 8 mg in the first 24 hours after laparoscopic cholecystectomy is almost the same.
Keywords: Postoperative nausea and vomiting; Dexamethasone; Ondansetron